Arterial dissections: Common features and new perspectives - Bax, Monique; Romanov, Valentin; Junday, Keerat; Giannoulatou, Eleni; Martinac, Boris; Kovacic, Jason C.; Liu, Renjing; Iismaa, Siiri E.; Graham, Robert M. (Frontiers in Cardiovascular Medicine, 2022)
Arterial dissections, which involve an abrupt tear in the wall of a major artery resulting in the intramural accumulation of blood, are a family of catastrophic disorders causing major, potentially fatal sequelae. Involving diverse vascular beds, including the aorta or coronary, cervical, pulmonary, and visceral arteries, each type of dissection is devastating in its own way. Traditionally they have been studied in isolation, rather than collectively, owing largely to the distinct clinical consequences of dissections in different anatomical locations – such as stroke, myocardial infarction, and renal failure. Here, we review the shared and unique features of these arteriopathies to provide a better understanding of this family of disorders. Arterial dissections occur commonly in the young to middle-aged, and often in conjunction with hypertension and/or migraine; the latter suggesting they are part of a generalized vasculopathy. Genetic studies as well as cellular and molecular investigations of arterial dissections reveal striking similarities between dissection types, particularly their pathophysiology, which includes the presence or absence of an intimal tear and vasa vasorum dysfunction as a cause of intramural hemorrhage. Pathway perturbations common to all types of dissections include disruption of TGF-β signaling, the extracellular matrix, the cytoskeleton or metabolism, as evidenced by the finding of mutations in critical genes regulating these processes, including LRP1, collagen genes, fibrillin and TGF- receptors, or their coupled pathways. Perturbances in these connected signaling pathways contribute to phenotype switching in endothelial and vascular smooth muscle cells of the affected artery, in which their physiological quiescent state is lost and replaced by a proliferative activated phenotype. Of interest, dissections in various anatomical locations are associated with distinct sex and age predilections, suggesting involvement of gene and environment interactions in disease pathogenesis. Importantly, these cellular mechanisms are potentially therapeutically targetable. Consideration of arterial dissections as a collective pathology allows insight from the better characterized dissection types, such as that involving the thoracic aorta, to be leveraged to inform the less common forms of dissections, including the potential to apply known therapeutic interventions already clinically available for the former.